Use of Functional Assessment to Define Therapeutic Goals and Treatment. Issue 9 (13th May 2019) - High, Kevin P.; Zieman, Susan; Gurwitz, Jerry; Hill, Carl; Lai, Jennifer; Robinson, Thomas; Schonberg, Mara; Whitson, Heather
Abstract : This article summarizes the presentations and discussions from a workshop, "Using Functional Assessment to Define Therapeutic Goals and Treatment, " which took place on November 30 to December 1, 2017. This workshop brought together transdisciplinary leaders in the fields of function and disability and clinical investigators engaged in research on geriatric populations to outline opportunities and challenges for incorporating measures of function in clinical research. Topics addressed included reliable and clinically feasible measures of function and key domains of health (eg, musculoskeletal, cognitive, and sensory) that are most strongly associated with patients' perceptions of well‐being, independence, and quality of life across a wide array of diseases and interventions. The workshop also focused on the importance of function in medical decision making to inform communications between specialty physicians and patients about prognosis and goals of care. Workshop participants called for more research on the role of function as a predictor of an intervention's effectiveness and an important treatment outcome. Such research would be facilitated by development of a core set of simple, short, functional measures that can be used by all specialties in the clinical setting to allow "big data" analytics and a pragmatic research. J Am Geriatr Soc 67:1782–1790, 2019